Penyuluhan dan Fasilitasi Pemilihan Umum Bagi Masyarakat Negeri Hatalai - Ronald D. Hukubun; Warnesy A Samangun; Poppy S Manila; Hensly Tahalea; Grisko V. Pattippeilohy; Anastasya Supusepa; Refaldy Siahaya; Sherly Lewerissa (Jurnal Insan Pengabdian Indonesia, 2023)
Indonesia is known as a multicultural country, where one of the cultures is traditional villages. Maluku is one of the provinces that is still very strong with great traditions and culture that still stands under the name of a traditional country, one of which is Negeri Hatalai. Even though Hatalai Country is still known as a traditional country and is still very strong, Hatalai Country itself cannot be separated from aspects of government administration, one of which is making the elections that will be held a success. It is very important for the public to know about general elections, especially first-time voters. One of the mandatory requirements for a holder of voting rights is ownership of population documents such as a Resident Identity Card (KTP). Thus, education is needed regarding the importance of elections for first-time voters as well as facilitating the creation of population documents considering the geographical conditions of Hatalai Country. This community service uses democratic education methods by means of lectures and discussions. The results of this service activity show that novice voters understand the importance of elections and how to make elections successful as seen from their activeness during the counseling, and are enthusiastic about making population documents, in this case KTP.